An investigation of the relationship between ageing in place and successful ageing in elderly individuals. Issue 4 (25th February 2020) - Yalcinoz Baysal, Hasret; Aktas, Betül; Bakan, Ayse Berivan
Abstract : Background: With the increase in longevity in the world, successful ageing has become an important issue. This study aims to investigate the relationship between ageing in place and successful ageing in elderlies. Methods: This study, which utilised a descriptive and relational‐screening model, was conducted with the participation of 370 individuals aged 65 and over who were registered in Family Health Centres in a city centre located in the eastern part of Turkey. Results: The participating elderlies' Successful Ageing Scale mean score was 54.16 ± 11.32, and the Ageing in Place Scale mean score was 54.24 ± 12.88. While there was a positive, statistically significant relationship between the Successful Ageing Scale total score, the Ageing in Place Scale total score, and living in the same environment, there was a negative, significant relationship between age and the Successful Ageing Scale total score. Conclusion: Elderlies' successful ageing processes are affected positively by the increase in the duration of living in the same environment and satisfaction level about the place they lived in. Successful ageing is negatively affected by the increase in age. It is recommended that elderly people's living environments should not be changed and their social support networks should be strengthened as much as possible so they can have a successful ageing process.